Health‐related quality of life in patients with melanoma expressed as utilities and disability weights. (1st December 2014) - Tromme, I.; Devleesschauwer, B.; Beutels, P.; Richez, P.; Leroy, A.; Baurain, J.‐F.; Cornelis, F.; Bertrand, C.; Legrand, N.; Degueldre, J.; Thomas, L.; Legrand, C.; et al.
Summary: Background: Few studies about health‐related quality of life (HRQoL) in patients with melanoma have expressed their results in terms of utilities or disability weights (DWs). Utilities are required for calculating quality‐adjusted life years and therefore for cost‐effectiveness analyses. DWs are useful to assess the burden of diseases through disability‐adjusted life years. Objectives: To provide utilities and DWs regarding patients with melanoma. Methods: The patients were classified into eight groups using four stages based on the 2009 American Joint Committee on Cancer stages, with each stage subdivided into treatment and remission phases. The EuroQoL Five Dimensions Five Levels (EQ‐5D‐5L) questionnaire was completed by the patients with melanoma to provide a mean utility for each group. In addition to this, the EuroQoL visual analogue scale (VAS) and a validated quality‐of‐life questionnaire dedicated to patients with melanoma [Functional Assessment of Cancer Therapy Melanoma (FACT‐M)] were completed by the same patients in order to compare their results with the obtained utilities. DWs were obtained by calculating, for each patient, the difference between his/her utility and the corresponding sex‐ and age‐specific population norm. Results: A total of 395 questionnaire sets were completed. Utilities and DWs showed significant differences between follow‐up groups. Treatment groups had similar utilities and DWs but these results were obtained during different treatment durations and therefore have different weights. The VAS and the FACT‐M were found to be less sensitive. Nevertheless, the FACT‐M identified some problems not found by the EQ‐5D‐5L questionnaire. Conclusions: The EQ‐5D‐5L questionnaire seems adequate to provide utilities and DWs in patients with melanoma. Lower HRQoL in female patients with melanoma is probably linked to lower HRQoL in the general population.